Flux pattern in 1000 kVA 11/.433 kV distribution transformer core to sinusoidal wave - Shahanom, Uthman; Ismail, Daut, Prof. Dr.; Dina Maizana, Maiz Ahmad, Ir. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.